2021
DOI: 10.1002/jemt.23708
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bio‐fabricated silver nanoparticles for distinct anti‐fungal activity against sugarcane phytopathogens

Abstract: Advanced research, development, and application of silver nanoparticles is proceeding in recent times due to their incredible utilization in various fields. Present study was focused on the production, characterization, and antifungal activities of silver nanoparticles (AgNPs). An environment friendly extracellular biosynthetic approach was adopted to produce the AgNPs by using bacteria, fungi, and sugarcane husk. Agents used for reduction of silver to nanoparticles were taken from culture filtrate of plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The IR spectral analysis of BOAgNPs with Carbapol 940 confirmed the occurrence of active groups such as O–H (stretching at 3341 cm −1 ), C = C (stretching at 1636 cm −1 ), C–H (stretching at 1451 cm −1 ) and C-O (stretching at 1230 cm −1 ) ( Amna et al, 2021 ). The observations suggested that mixing BOAgNPs with polymer (Carbapol 940) did not produce any chemical change.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The IR spectral analysis of BOAgNPs with Carbapol 940 confirmed the occurrence of active groups such as O–H (stretching at 3341 cm −1 ), C = C (stretching at 1636 cm −1 ), C–H (stretching at 1451 cm −1 ) and C-O (stretching at 1230 cm −1 ) ( Amna et al, 2021 ). The observations suggested that mixing BOAgNPs with polymer (Carbapol 940) did not produce any chemical change.…”
Section: Discussionmentioning
confidence: 90%
“…The SEM analysis in the current study revealed that the particle size is a spherical shape. Such types of particles according to previous studies give a smooth texture to the formulation ( Amna et al, 2021 ). Besides, the particle size in the range of 50 – 110 µm was reported to be ideal for a drug molecule to achieve its intended therapeutic activity ( Das et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There is a lot of documents on the antifungal activity of AgNPs. In the most recent successes, in 2021, Amna et al [116] proved the prominent role of AgNPs against Colletotrichum falcatum and Fusarium moniliforme, fungal pathogens of sugarcane. Also, Al-Otibi et al [117] exhibited reduced growth mycelia of several plant pathogenic fungi, Helminthosporium rostratum, Fusarium solani, Fusarium oxysporum, and Alternaria alternata, exposed to bio-fabricated AgNPs using Cheeseweed mallow.…”
Section: Nanomaterials For Application In Pesticidesmentioning
confidence: 99%